21-cm constraints on spinning primordial black holes. Issue 3 (1st March 2022) - Cang, Junsong; Gao, Yu; Ma, Yin-Zhe
Abstract: Hawking radiation from primordial black holes (PBH) can ionize and heat up neutral gas during the cosmic dark ages, leaving imprints on the global 21-cm signal of neutral hydrogen. We use the global 21-cm signal to constrain the abundance of spinning PBHs in mass range of [2 × 10 13, 10 18 ] grams. We consider several extended PBH distribution models. Our results show that 21-cm can set the most stringent PBH bounds in our mass window. Compared with constraints set by Planck cosmic microwave background (CMB) data, 21-cm limits are more stringent by about two orders of magnitudes. PBHs with higher spin are typically more strongly constrained. Our 21-cm constraints for the monochromatic mass distribution rule out spinless PBHs with initial mass below 1.5 × 10 17 g, whereas extreme Kerr PBHs with reduced initial spin of a 0 =0.999 are excluded as the dominant dark matter component for masses below 6 × 10 17 g. We also derived limits for the log-normal, power-law and critical collapse PBH mass distributions.